Analisis Pengaruh Earning Power, dan Kepemilikan Manajerial Terhadap Manajemen Laba Dengan Keputusan Investasi Sebagai Variabel Moderasi : Sub Sektor Telekomunikasi yang Terdaftar di BEI Periode 2018-2021 - Damayanti, Alvina; Prajawati, Maretha Ika (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2022)
The purpose of this study is to understand the effect of earning power, managerial ownership on earnings management, with investment decisions as a moderator. Telecommunications companies listed on the Indonesia Stock Exchange between 2018 and 2021 are the sample of the study. Seven telecommunications businesses were collected for the research sample through the use of purposive sampling, and according to the required qualifications. The model used is quantitative research. The analysis carried out includes the use of descriptive statistics, inferential statistics and hypothesis testing. Data management for the study was carried out using SmartPLS 3 software. The findings of the investigation revealed that: (1) earning power had a negative and significant effect on earnings management, (2) earning power had a negative and insignificant effect on investment decisions, (3) investment decisions had a negative effect. and not significant to earnings management. (4) Investment decisions are not able to moderate the effect of earning power on earnings management. (5) Investment decisions are not able to moderate the effect of managerial ownership on earnings management.